THE DYNAMICS OF SOCIAL ECONOMIC LIFE OF MOTOR RICKSHAW DRIVERS AMID THE DEVELOPMENT OF ONLINE TRANSPORTATION IN MAKASSAR CITY - Mardania, Mardania (UNM Geographic Journal, 2022)
This study aims to (1) describe the dynamics of the socio-economic life of motorized rickshaw riders in the city of Makassar (2) find out the problems caused by online transportation to the life of online transportation in Makassar City. The type of research used in this research is descriptive qualitative. The data collection techniques in this study were using the methods of observation, interviews, and documentation, then analyzed with qualitative descriptive techniques.  The results showed that (1). The description of the dynamics of the socio-economic life of motorized rickshaw drivers in Makassar City, namely work, income, education and family. The work is categorized as "very good" because for the motor rickshaw rider itself, it requires ability/skill, motivation, and quality of work. Education is categorized enough in terms of education level and family education. income is sufficient to meet daily needs even though it is mediocre, namely basic income, additional income and overall income. families of motorized rickshaw riders live in harmony because of good family members, good quality time and good responsibilities (2) The problem caused by online-based transportation on the dynamics of the socio-economic life of motorized rickshaw riders in Makassar City is that the increase in poverty is categorized as high because it can decrease revenue and loss of passengers. The number of unemployed is increasingly being categorized as "very high" because it can eliminate jobs and make finding new jobs for motorized rickshaw drivers. Social conflicts have occurred, namely the seizure of the base but the involvement of the security forces is not prominent in handling conflicts that occur between motorized rickshaw riders and online transportation.